Effects of nano mineral-supplemented diet on pig growth - Son, Hoang Nghia (Academia Journal of Biology, 2020)
This paper examined the effects of nano mineral supplementation of diets on the growth of pigs. The total of 180 pigs used for this study were classified into 4 experimental groups and one control group. The results showed that the weight of pigs at the beginning and the end of the experiment was insignificantly different between experimantal and control groups. The same daily gain weight was observed between experimental and control groups. However, the feed conversion ratio (FCR) of four experimental groups I, II, III and IV is 3.00 ± 0.28, 2.95 ± 0.11, 2.85 ± 0.19 and 2.90 ± 0.24, respectively, that were lower than of the control groups, i.e. 3.17 ± 0.42. The mineral content of Fe, Cu, Zn and Mn in liver of pigs in all the experimental groups is lower than that in liver of pigs in the control group. In addition, the amount of Fe and Zn metal in urine and feces of the experimental groups is also lower than in the control group. The results of our study showed that the addition of nano minerals in diets for pigs not only reduced the feed conversion ratio in pigs, also decreased the amount of minerals releasing into the environment.